Multiplex base- and prime-editing with drive-and-process CRISPR arrays - Yuan, Qichen; Gao, Xue (Nature communications, 2022)
Current base- and prime-editing technologies lack efficient strategies to edit multiple genomic loci simultaneously, limiting their applications in complex genomics and polygenic diseases. Here, we describe drive-and-process (DAP) CRISPR array architectures for multiplex base-editing (MBE) and multiplex prime-editing (MPE) in human cells. We leverage tRNA as the RNA polymerase III promoter to drive the expression of tandemly assembled tRNA-guide RNA (gRNA) arrays, of which the individual gRNAs are released by the cellular endogenous tRNA processing machinery. We engineer a 75-nt human cysteine tRNA (hCtRNA) for the DAP array, achieving up to 31-loci MBE and up to 3-loci MPE. By applying MBE or MPE elements for deliveries via adeno-associated virus (AAV) and lentivirus, we demonstrate simultaneous editing of multiple disease-relevant genomic loci. Our work streamlines the expression and processing of gRNAs on a single array and establishes efficient MBE and MPE strategies for biomedical research and therapeutic applications. Current base- and prime-editing technologies lack efficient strategies to edit multiple genomic loci simultaneously, limiting their applications in complex genomics and polygenic diseases. Here the authors describe drive-and-process CRISPR array architectures for multiplex base-editing and multiplex prime-editing in human cells.